Oxytocin Sustained Release Using Natural Rubber Latex Membranes - Barros, Natan Roberto de [UNESP] (2016)
The demand for biomaterials with properties that provide sustained release of substances with pharmacological interest is constant. One candidate for applications in this area is the Natural Rubber Latex (NRL) extracted from the rubber tree Hevea brasiliensis. Recent studies indicate the NRL as a matrix for sustained release, showing promising results for biomedical applications such as: can stimulate natural angiogenesis and is capable of adhering cells on its surface, promoting the replacement and regeneration of tissue. So, the NRL is an excellent candidate to propitiate the sustained release of peptides of pharmacological interest such as oxytocin, a hormonal peptide which has the function to promote uterine muscle contractions and reduce bleeding during childbirth, and stimulate the release of breast milk. Results demonstrated that 90 mu g mL(-1) (45 %) of the incorporated peptide in Natural Rubber Latex Biomedical (NRLb) functionalized membranes was released at 10 h in phosphate-buffered saline (PBS) solution. Swelling kinetics assay showed that the NRLb membranes are able to absorb over a period of 16 h up to 1.08 grams of water per grams of membrane. Scanning electron microscopy showed that the peptide was adsorbed on the surface and within NRLb membrane. Fourier transform infrared and Derivative Thermogravimetric analysis indicated that oxytocin did not interacted chemically with the membrane. Furthermore, hemolysis of erythrocytes, quantified spectrophotometrically using materials (Oxytocin, NRLb, and NRLb + Oxytocin) showed no hemolytic effects up to 100 mu g mL(-1) (compounds and mixtures), indicating no detectable disturbance of the red blood cell membranes. Based on these results it was possible to conclude that the NRLb has shown effectiveness as a model in the release of peptides with pharmacological interest.